Sociology for health professionals - Russell, Lani (SAGE, 2014)
Sociology is a core topic for all trainee health professionals, but many struggle to get to grips with it and to see what sociology has to offer. Based on years of experience teaching sociology to health care students, Lani Russell has written a truly introductory text which explains the main sociological concepts without jargon or becoming too advanced. Using carefully chosen examples, she shows how health issues are influenced by social phenomena such as class, race or sexuality and the relevance this has for practitioners